The littlest dinosaur - "Dicks, Terrance" (Puffin: London, 1995)
In the first of two stories, twins Oliver and Eleanor acquire a huge, dusty egg in a junk shop and soon a baby dinosaur hatches out. They discover their pet is an echidna, the size of a chicken. In the second story, Littlest the dinosaur helps the twins with a problem.
Keywords: Dinosaurs-English Fiction